MISSIO DEI INKARNASIONAL: Kerangka Teologis Bagi Misi Holistik Lintas Budaya Di Indonesia - Sostenis Nggebu; Raphael Buyung; Paulus Jinu Kim; Yopie F.M. Buyung; Yusnoveri Chung (SEKOLAH TINGGI TEOLOGI INJILI SETIA SIAU, 2025)
The concept of Missio Dei is rooted in the mission of the Triune God who sends and calls the Church to participate in the work of redemption and restoration of the world in a cross-cultural and holistic manner. However, within Indonesia’s pluralistic context, there remains a theological need to articulate a contextual understanding of Missio Dei, particularly in relation to reaching marginalized and unreached people groups. This study aims to explicate the theological foundations of Missio Dei and to formulate incarnational and holistic principles as a conceptual framework for mission that is relevant within Indonesia’s socio-cultural plurality. Employing a qualitative-descriptive approach through a literature-based study in theology and missiology, this research involves theological-conceptual analysis, critical examination of incarnational principles grounded in the kenosis of Christ, holistic principles oriented toward shalom, and contextual interpretation within the Indonesian setting. The findings indicate that Missio Dei must be understood through an incarnational approach that emphasizes contextualization of the Gospel and respect for local epistemologies, as well as a holistic approach aimed at the restoration of the totality of human life. This study contributes by offering an incarnational-holistic theological framework as a reflective foundation for the development of ethical, contextual, and transformative cross-cultural mission praxis in Indonesia.